Life Skills Education Strategy to Prepare Students to Face Global Challenges - Jakfar, Rusnadi; Tumin; Thaufiq, Mohamad (Jurnal Pendidikan Nusantara, 2025)
This study aims to describe the implementation of life skills education, the integration of teaching and extracurricular activities, the development of specific and generic skills, and efforts to support students' life skills. Data collection methods were conducted through interviews, observations, and document analysis. Interviews were conducted with the head of staff of Kuliyatul Mu'alimin al-Islamiyah (KMI). The data analysis technique in this study uses three stages, namely, data reduction, data presentation, and conclusion drawing. The results showed that this cottage applies two main skills in life skills education, namely specific skills related to certain fields and generic skills that can be used in various aspects of life. The implementation of life skills education is carried out by integrating curricular and extracurricular learning activities, which shows that this education has been systematically organized in the curriculum set by the cottage. In conclusion, the implementation of life skills education at Pondok Modern Darussalam Gontor Campus 5 Darul Muttaqin Banyuwangi runs effectively. It makes a significant contribution to the development of santri skills so that they are ready to face challenges in society. It is expected to be a reference for other educational institutions developing similar academic programs.